Associations Between Local Health Department Expenditures on Foundational Capabilities and PHAB Accreditation Standards Scores - Dada, Oluwatosin O.; Bekemeier, Betty; Flaxman, Abraham; de Castro, A. B. (Frontiers in Public Health, 2022)
Context: Foundational Capabilities (FC) are the public health (PH) infrastructure areas that are essential for local health departments (LHDs) to support a “minimum package” of programs and services that promote population health. Despite being a critical component of LHD programs, FC are chronically underfunded, and studies on the relationship between LHD FC expenditures and their performance – the LHDs’ ability to provide essential PH programs and services to their community – have not been previously reported. Public Health Accreditation Board (PHAB) accreditation is a nationally recognized accreditation program for PH agencies. PHAB accreditation assesses LHDs’ performance against sets of standards that are based on the ten essential PH services. Alignment between FC and the PHAB standards presents a means for assessing LHD FC expenditures relative to their performance in PHAB accreditation standards. Objectives: We examined the association between LHD total FC expenditures, as well as FC funding allocation patterns, and performance score on selected PHAB accreditation standards. Methods: We used Bayesian regression methods to estimate the coefficients for the aggregate performance score, and performance scores on individual PHAB standards. Results: Analyses showed that a dollar increase in total FC expenditures is associated with a 0.2% increase in the aggregate performance score in selected PHAB standards as well as the performance score on most of the standards examined. LHDs that allocated FC budgets more evenly across FC programs were found to be more likely to have higher scores. Conclusions: Investment in FC could improve LHD performance score in PHAB accreditation standards and support LHDs’ capability for improving community health outcomes. Allocating available FC resources across the various FC programs could support better LHD performance, as indicated by accreditation scores. This study contributes to advancing the understanding of public health finances in relation to performance and could help guide effective LHD resource allocation.